2014
DOI: 10.4161/cc.28475
|View full text |Cite
|
Sign up to set email alerts
|

CRABP1 provides high malignancy of transformed mesenchymal cells and contributes to the pathogenesis of mesenchymal and neuroendocrine tumors

Abstract: CRABP1 (cellular retinoic acid binding protein 1) belongs to the family of fatty acid binding proteins. Retinoic acid binding is the only known functional activity of this protein. The role of CRABP1 in human carcinogenesis remains poorly understood. Here, for the first time we demonstrated pro-metastatic and pro-tumorigenic activity of CRABP1 in mesenchymal tumors. Further functional analysis revealed that the pro-tumorigenic effect of CRABP1 does not depend on retinoic acid binding activity. These results su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 47 publications
0
25
1
7
Order By: Relevance
“…The high throughput mRNA sequencing analysis revealed that a total of 262 genes (159 up-regulated, and 103 down-regulated) was differentially expressed (Fold change (log2) > 2 and P-value < 0.05) in the shCIC-3 PC-3 cells compared with control cells ( Supplementary Table 2 ). Among the differentially expressed genes, cellular retinoic acid binding protein 1 ( CRABP1 ) primarily caught our attention, because of the highest fold increase upon knock-down of CIC in PC-3 cells ( Supplementary Table 2 ) and its previously known pro-tumorigenic and pro-metastatic activity in mesenchymal tumors [ 18 ]. Moreover, it is known that CRABP1 is overexpressed in castration-resistant prostate cancer cells [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…The high throughput mRNA sequencing analysis revealed that a total of 262 genes (159 up-regulated, and 103 down-regulated) was differentially expressed (Fold change (log2) > 2 and P-value < 0.05) in the shCIC-3 PC-3 cells compared with control cells ( Supplementary Table 2 ). Among the differentially expressed genes, cellular retinoic acid binding protein 1 ( CRABP1 ) primarily caught our attention, because of the highest fold increase upon knock-down of CIC in PC-3 cells ( Supplementary Table 2 ) and its previously known pro-tumorigenic and pro-metastatic activity in mesenchymal tumors [ 18 ]. Moreover, it is known that CRABP1 is overexpressed in castration-resistant prostate cancer cells [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…SCG2 encodes for secretogranin, among the NE markers identified in prostate small cell carcinomas by a molecular characterization study that highlighted a diverse repertoire of genes reflecting characteristics of their NE cell of origin [45]. CRABP1 has a pro-tumorigenic and a pro-metastatic activity in mesenchymal and neuroendocrine tumors [46]. SLC35D3, which showed a dramatic up-regulation also in NEPC PDXs from the independent dataset GSE59984 (data not shown), is specifically expressed in the substantia nigra, striatum, and olfactory bulb in mouse brain and it functions as an ER chaperone for dopamine receptor D1 trafficking to the plasma membrane [47].…”
Section: Discussionmentioning
confidence: 99%
“…CRABP1 (Cellular retinoic acid-binding protein 1) is responsible for binding retinoic acid transporting it into cells. Evidence for its role in carcinogenesis is controversial, showing both pro-apoptotic and pro-metastatic properties in vitro (Kainov et al, 2014;Persaud et al, 2016). Its hypermethylation and/or underexpression has been described in colorectal, breast, ovarian, esophageal and cervical cancers (Tanaka et al, 2007;Miyake et al, 2011;Liu et al, 2015;Arellano-Ortiz et al, 2016;Cha et al, 2016).…”
Section: Receptorsmentioning
confidence: 99%